2003
DOI: 10.1038/sj.eye.6700489
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of telemedicine for diagnosing and managing eye problems in accident and emergency departments

Abstract: Objectives To assess the accuracy and efficiency of telemedicine in diagnosing and managing eye problems presenting to accident and emergency departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…3840,42,45,4749,53 Some research did not include sensitivity analyses 43,46,51,53,54 and some research describes implementation of technologies rather than validation. 43,46,48,52,53 Portable anterior segment photography with mobile phone camera devices has been evaluated. 41,44 Barsam and colleagues provided a descriptive technique of anterior segment slit lamp photography with the iPhone.…”
Section: Discussionmentioning
confidence: 99%
“…3840,42,45,4749,53 Some research did not include sensitivity analyses 43,46,51,53,54 and some research describes implementation of technologies rather than validation. 43,46,48,52,53 Portable anterior segment photography with mobile phone camera devices has been evaluated. 41,44 Barsam and colleagues provided a descriptive technique of anterior segment slit lamp photography with the iPhone.…”
Section: Discussionmentioning
confidence: 99%
“…In another study involving a range of eye problems, in-person examinations using slit lamps were compared with remote video examinations at 384 Kbps using slit lamps or torchlight. 12 The percentage of clinically important disagreement was the same for the slit lamp conditions (just 5% of cases), but doubled with torchlight. A third slit lamp strabismus assessment study found full agreement in 80% of the cases, but the 384 Kbps transmission rate was a problem in cases involving micro-eye movements.…”
Section: Ahrq Specialty Studiesmentioning
confidence: 89%
“…11,12 Otolaryngology diagnoses were similar when outputs from local audiometric devices were transmitted. 19 The only difference in the otolaryngology 17 and gastroenterology 22,23 DETERMINING THE RELEVANCY OF TELEMEDICINE studies involving endoscopes or otoscopes 32 concerned transmitting local video for remote consultation.…”
Section: Telemedicine Application Principlesmentioning
confidence: 94%
See 1 more Smart Citation
“…The study demonstrated that accident and emergency teleconsultations can be technically reliable and effective in reducing the number of patient transfers and in a manner acceptable to the referring clinicians. Similarly, Bowman et al [59] conducted a controlled trial to assess the accuracy of telemedicine in diagnosing and managing eye problems presented to accident and emergency. The study has shown that telemedicine, utilizing video slit lamp images, to be an effective, safe, and accurate method of diagnosing and managing these patients.…”
Section: Discussionmentioning
confidence: 99%